Synthesis and third order nonlinear optics of a new soluble conjugated porphyrin polymer - Screen, T; Lawton, K; Wilson, G; Dolney, N; Ispasoiu, R; Goodson, T; Martin, S; Bradley, D; Anderson, H (2001)
The synthesis of a new soluble conjugated porphyrin polymer 4 is reported. The MALDI TOF mass spectrum shows the presence of oligomers with up to 13 repeat units and GPC gives a Mn of 53 kDa. The electronic absorption spectra of this polymer exhibit an intense Q band at 800 nm in solution and 853 nm in the solid state, demonstrating a high degree of conjugation. Electroabsorption spectroscopy shows that thin films of 4 have lower resonant third order NLO susceptibility than our previous conjugated porphyrin polymer 2, whereas closed z-scan measurements indicate that the off-resonance real susceptibility, at 1064 nm, is exceptionally large for both polymers (χ(3)R =-2 × 10-16 m2 V-2). Open z-scan measurements were also made at 1064 nm, demonstrating that the two polymers exhibit similar nonlinear absorption at this wavelength (β= 1 cm GW-1 at 0.2 mM concentration).